Antioxidant, Antimicrobial and Cosmeceutical Potential of Wild Mushroom Extracts - Tânia Martins; Liliana Machado-Carvalho; Alfredo Aires; Maria José Saavedra; Guilhermina Marques (Applied Microbiology, 2023)
Macrofungi have been previously studied for their nutritional value and medicinal properties. However, despite wild mushrooms being a great source of beneficial bioactive compounds, the literature exploring their biotechnological application as nutraceuticals, cosmeceuticals and nutricosmetics is scarce. In this work, the species Butyriboletus regius, Ganoderma lucidum, Inonotus hispidus, Lanmaoa fragrans, Pisolithus tinctorius, Suillellus luridus, Suillellus mendax and Xerocomus subtomentosus were characterized according to their phenolic composition, antioxidant capacity, antimicrobial activity and cosmeceutical potential. For that purpose, dried and ground mushrooms were extracted with ethanol (40% v/v) using ultrasound-assisted extraction. Of the eight mushrooms analyzed, I. hispidus and P. tinctorius stood out for their high content of phenolic compounds, high antioxidant capacity and anti-hyaluronidase activity. Regarding antimicrobial activity, both mushrooms showed good inhibition of bacterial growth and bactericidal activity, especially on Gram-positive bacteria; however, L. fragans obtained the best results. Cream formulations with I. hispidus and P. tinctorius extracts in their composition improved their antioxidant activity. These results indicate that I. hispidus and P. tinctorius can be proposed as a new potential source of natural compounds with application in the cosmetic industry.